Associations of Individual Characteristics and Nutritional Status with Hypertension in Adults - Nisa, Hoirun; Pratiwi, Safira Hani; Nasution, Erlina (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: Hypertension is a significant health problem and a modifiable risk factor for cardiovascular diseases. The prevalence of hypertension in adults continues to increase at a global and national level. Information regarding determinants of hypertension is critical for preventive measures, especially in adults. This study examined the associations of individual characteristics and nutritional status with hypertension in adults in East Ciputat, South Tangerang.Method: A cross-sectional study was conducted to 400 adults aged ≥35 years old. Data on their blood pressure and nutritional status (body mass index) were obtained by measurement, and data on individual characteristics, food consumption, and lifestyle were collected through an interview using a structured questionnaire. A multivariate analysis was performed using a logistic regression test. Results: The proportion of hypertension was 54%. The multivariate analysis results showed that older age, low education level, a family history of hypertension, overweight/obese status, and consumption of sweet foods for >3 times/week increased the risk of hypertension (Odds Ratio 2.37-11.28). In conclusion, people aged ≥65 years were at the greatest risk of hypertension. This study highlights the importance of increasing health promotion on the modifiable risk factors of hypertension such as food consumption patterns, weight control, and knowledge about hypertension.